2021
DOI: 10.2217/bmm-2020-0876
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of Mris Predicts Osteosarcoma Chemoresponsiveness

Abstract: Aim: This study aimed to improve osteosarcoma chemoresponsiveness prediction by optimization of computational analysis of MRIs. Patients & methods: Our retrospective predictive model involved osteosarcoma patients with MRI scans performed before OsteoSa MAP neoadjuvant cytotoxic chemotherapy. Results: We found that several monofractal and multifractal algorithms were able to classify tumors according to their chemoresponsiveness. The predictive clues were defined as morphological complexity, homogeneity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 24 publications
(31 reference statements)
3
14
0
Order By: Relevance
“…By the irregular ROI approach, this study indicated that 1-D Dh could extract useful predictive information only from tumour tissue, based on the result that analysis of entire images, without ROI, did not provide any signi cant predictive performance. This result was in line with the previous investigation showing the bene cial in uence of ROI delineation on the predictive performance of 2-D fractal analysis 10 .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…By the irregular ROI approach, this study indicated that 1-D Dh could extract useful predictive information only from tumour tissue, based on the result that analysis of entire images, without ROI, did not provide any signi cant predictive performance. This result was in line with the previous investigation showing the bene cial in uence of ROI delineation on the predictive performance of 2-D fractal analysis 10 .…”
Section: Discussionsupporting
confidence: 93%
“…2-D fractal analysis is also non-directional, but unlike 1-D Dh, it is not fully compatible with irregular ROI. This comparison indicated that the ideal compatibility of 1-D Dh with irregular ROI only offers a slight improvement in predictive performance over the previously reported 2-D box-counting 10 . There are no previous tumour morphology studies that could be directly compared to the tumour MRI analysis reported here.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations